Strategi Penguatan Identitas Produk dan Akses Pasar Usaha Mikro, Kecil, dan Menengah (UMKM) Raja Basreng: Studi Kasus: KKN Kelompok 4 di Kp. Tapos Udik RT. 002/ RW. 002 Desa Tapos 1 Kecamatan Tenjolaya Kabupaten Bogor - Somantri, Fikri Indriana; Novita, Evi; Supriyatna, Rio Kartika; Junaedi, Dedi; Wijaya, Siska Putri; Iskandar, Nandang; Rahmawati, Dian; Putri, Sardiani; Fikri, M. Chairil; Murtafiah, Fifih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
UMKM play a central role in driving local economies, yet they often face challenges in building a strong product identity and effectively expanding market access. This study aims to identify and analyze strategies that can be implemented to strengthen product identity and market access for UMKMs, using a case study of the